Role of fiscal policy for private investment in Pakistan - Ghulam Rasool Madni (International Journal of Economic Sciences and Applied Research, 2014)
Fiscal policy has much controversial debate regarding its effectiveness on private investment. Taxation and government expenditure are two main instruments of fiscal policy. This paper is aimed to analyze the effect of fiscal deficit and other variables on private investment of Pakistan. The data time span for this study is 1979-2012. After finding the integration order of all variables by Augmented Dicky Fuller Test, the impact of variables is analyzed by utilizing the Auto Regressive Distributed Lag approach of Cointegration which is a better estimation technique for small sample size. Error Correction Model is applied for short run dynamics. The results reveal that fiscal deficit, rate of interest, inflation and external debt are affecting negatively the private investment in Pakistan while exchange rate and exports have a positive impact on private investment.
Keywords: E62; C22; 330; Fiscal Policy; Private Investment; co integration